SYN-EXHUMATION COUPLING OF OCEANIC AND CONTINENTAL UNITS ALONG THE WESTERN EDGE OF THE ALPINE CORSICA: A REVIEW - Di Rosa, Maria; Frassi, Chiara; Malasoma, Alessandro; Marroni, Michele; Meneghini, Francesca; Pandolfi, Luca (Ofioliti, 2021)
The Alpine Corsica represents a segment of the Alpine collisional belt. In its western edge, it is characterized by the close association of continental units deformed under high-pressure metamorphic conditions (Lower Units) and oceanic units showing a metamorphism ranging from high-pressure (Schistes Lustrés Complex) to very low-grade conditions (Upper Units). This paper provides a complete review of the relationships between the continental and oceanic units in selected five areas where the stratigraphic features, deformation history, metamorphic P-T path and tectonic setting are available for each unit. The collected data indicate that the oceanic units occur not only at the top of the continental ones, as generally proposed in the literature, but also intercalated within them. Such relationships were achieved at shallow structural level during the late stage of exhumation, when the continental units were tectonically coupled with the oceanic units which were dragged as slices from the orogenic wedge. The coupling probably occurred immediately before the transition from syn- to post-orogenic geodynamic regime that affected the whole Alpine-Apennine collisional system in the early Oligocene. After the coupling, the stack of oceanic and continental units experienced a further exhumation-related deformation before their final exposure at the surface.